The future of evolutionary medicine: sparking innovation in biomedicine and public health - Natterson-Horowitz, B.; Aktipis, Athena; Fox, Molly; Gluckman, Peter D.; Low, Felicia M.; Mace, Ruth; Read, Andrew; Turner, Paul E.; Blumstein, Daniel T. (Frontiers in Science, 2023)
Evolutionary medicine – i.e. the application of insights from evolution and ecology – has tremendous untapped potential to spark transformational innovation in biomedicine and inform effective health policies. Fundamentally, a systematic mapping across the full diversity of life is required to identify animal model systems for disease vulnerability, resistance and counter-resistance that could lead to novel clinical treatments. Evolutionary dynamics should guide the development of novel therapeutic approaches that target the development of treatment resistance in cancers (e.g. via adaptive or extinction therapy) and antimicrobial resistance (e.g. via innovations in chemistry, antimicrobial usage, and phage therapy). With respect to public health, the insight that many modern human pathologies (e.g. obesity) result from mismatches between the ecologies in which we evolved and our modern environments has important implications for disease prevention. Life-history evolution can also shed important light on patterns of disease burden, for example in reproductive health. Experience during the COVID-19 (SARS-CoV-2) pandemic has underlined the critical role of evolutionary dynamics (e.g. with respect to virulence and transmissibility) in predicting and managing this and future pandemics, and in using evolutionary principles to understand and address aspects of human behavior that impede biomedical innovation and public health (e.g. unhealthy behaviors and vaccine hesitancy). In conclusion, greater interdisciplinary collaboration is vital to systematically leverage the insight-generating power of evolutionary medicine to better understand, prevent and treat existing and emerging threats to human, animal and planetary health.